Influence of body position when considering the ecological validity of laboratory time-trial cycling performance - Jobson, S. A.; Nevill, A. M.; George, S. R.; Jeukendrup, A. E.; Passfield, L. (Journal of Sports Sciences, 2008)
The aims of this study were to compare the physiological demands of laboratory- and road-based time-trial cycling and to examine the importance of body position during laboratory cycling. Nine male competitive but non-elite cyclists completed two 40.23-km time-trials on an air-braked ergometer (Kingcycle) in the laboratory and one 40.23-km time-trial (RD) on a local road course. One laboratory time-trial was conducted in an aerodynamic position (AP), while the second was conducted in an upright position (UP). Mean performance speed was significantly higher during laboratory trials (UP and AP) compared with the RD trial (P < 0.001). Although there was no difference in power output between the RD and UP trials (P > 0.05), power output was significantly lower during the AP trial than during both the RD (P = 0.013) and UP trials (P = 0.003). Similar correlations were found between AP power output and RD power output (r = 0.85, P = 0.003) and between UP power output and RD power output (r = 0.87, P = 0.003). Despite a significantly lower power output in the laboratory AP condition, these results suggest that body position does not affect the ecological validity of laboratory-based time-trial cycling.